HER2: An emerging biomarker in non-breast and non-gastric cancers. Issue 3 (August 2015) - Omar, Norhayati; Yan, Benedict; Salto-Tellez, Manuel
Abstract: Introduction: HER2, a member of the human epidermal growth factor (HER) family of transmembrane tyrosine kinases, has been of considerable interest in oncology due to its significant role in the pathogenesis of various cancer types. Materials and methods: In this article, we review current data on HER2 as a potential biomarker in cancers other than breast and gastric by conducting an electronic database search using Pubmed. Results: The existing literature provides evidence that HER2 protein overexpression and genomic alterations exist in a subset of patients with non-breast and non-gastric cancers, and hints at the promise of anti-HER2 targeted therapy in these patients. Conclusion: Moving forward, the rigorous evaluation of HER2 (protein and genomic) status as a predictive biomarker will be necessary to bring anti-HER2 therapeutics for non-breast and non-gastric cancers to the clinic.